2016
DOI: 10.1007/s10620-016-4176-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Upper Gastrointestinal Cancer Occurrence After Endoscopy that Did Not Diagnose Cancer

Abstract: PEUGIC occurs in 6.7 % of UGIC. PEUGIC was associated with GC, younger age, female gender, increasing comorbidity and deprivation, and a lack of alarm symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
1
22
2
Order By: Relevance
“…This last association had been detected in previous investigations and may be explained by the partial mucosal healing of small mucosal lesions in the distal third of the oesophagus by PPI therapy 25 , 26 . Female gender, younger age, non‐gastroenterologist endoscopist and increasing comorbidity have also been postulated to increase the likelihood of interval upper gastrointestinal cancer 9 , 10 , 12 . Noticeably, neither our study (20% MEC versus 33% non‐MEC, p = 0.16) nor other investigations have proven that sedation is related to MEC, but some data indicate that moderate sedation increases UGE examination quality and patient satisfaction 27 .…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…This last association had been detected in previous investigations and may be explained by the partial mucosal healing of small mucosal lesions in the distal third of the oesophagus by PPI therapy 25 , 26 . Female gender, younger age, non‐gastroenterologist endoscopist and increasing comorbidity have also been postulated to increase the likelihood of interval upper gastrointestinal cancer 9 , 10 , 12 . Noticeably, neither our study (20% MEC versus 33% non‐MEC, p = 0.16) nor other investigations have proven that sedation is related to MEC, but some data indicate that moderate sedation increases UGE examination quality and patient satisfaction 27 .…”
Section: Discussionmentioning
confidence: 69%
“…Other physician‐related factors that have been proposed to explain missed cancers in UGE are not to biopsy benign‐like lesions, the presence of oesophagitis, obtaining an insufficient number of biopsies, pathological errors or follow‐up delay 12 , 13 . This reinforces the idea that every stricture, ulcer or non‐specific oesophageal mucosal abnormality should be biopsied and closely monitored 11 , 28 .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, improving current services by means of improving quality of gastroscopy and follow-up clinical care in the endoscopy unit should be a target of improvement. A study by Cheung et al 8 in the UK revealed that the ‘missed’ UGI cancer rate among patients who had a gastroscopy in the preceding 12–36 months was 6.7%. This study also suggests that patients with recurrent reflux symptoms were three times more likely to have a malignancy compared with symptoms such as dysphagia.…”
Section: Discussionmentioning
confidence: 99%